Comparative pharmacokinetics of four major compounds after oral administration of Mori Cortex total flavonoid extract in normal and diabetic rats - Xiong, Shan; Li, Xiaofan; Chu, Haiping; Deng, Zhipeng; Sun, Linying; Liu, Jia; Mu, Yanling; Yao, Qingqiang (Frontiers in Pharmacology, 2023)
Mori Cortex has been used in traditional Chinese Medicine as an antidiabetic agent. The aim of this study was to establish a UPLC-MS/MS method for simultaneous determination of morin, morusin, umbelliferone and mulberroside A in rat plasma and investigate the pharmacokinetics differences between normal and diabetic rats following oral administration of Mori Cortex total flavonoid extract. Samples were pre-treated by protein precipitation and genkwanin was used as internal standard. Chromatographic separation was performed using a Hypersil GOLD C18 column (50 mm × 2.1 mm, 3 μm). The mobile phase consisted of acetonitrile and water (containing 0.1 % formic acid) in gradient mode at a flow rate of 0.5 mL/min. The transitions of m/z 300.9→107.1, m/z 419.3→297.1, m/z 160.9→77.0, m/z 567.1→243.2 and m/z 283.1→268.2 were selected for morin, morusin, umbelliferone, mulberroside A and IS, respectively. The intra- and inter-day precision for analytes were less than 12.5% and the accuracy ranged from -8.1% to 3.5%. The extraction recovery was > 88.5% and no obvious matrix effect was observed. The AUC(0-t) and Cmax of morin were 501.3 ± 115.5 ng/mL*h and 127.8 ± 56.0 ng/mL in normal rats and 717.3 ± 117.4 ng/mL*h and 218.6 ± 33.5 ng/mL in diabetic rats. Meanwhile, the AUC(0-t) and Cmax of morusin were 116.4 ± 38.2 ng/mL*h and 16.8 ± 10.1 ng/mL in normal rats and 325.0 ± 87.6 ng/mL*h and 39.2 ± 5.9 ng/mL in diabetic rats. For umbelliferone and mulberroside A, the AUC(0-t) and Cmax also increased significantly in diabetic rats (p < 0.05). The validated method was successfully applied to the pharmacokinetic study in normal and diabetic rats.